Consensus Statement on Inpatient Use of Continuous Glucose Monitoring. (September 2017) - Wallia, Amisha; Umpierrez, Guillermo E.; Rushakoff, Robert J.; Klonoff, David C.; Rubin, Daniel J.; Hill Golden, Sherita; Cook, Curtiss B.; Thompson, Bithika; ,
In June 2016, Diabetes Technology Society convened a panel of US experts in inpatient diabetes management to discuss the current and potential role of continuous glucose monitoring (CGM) in the hospital. This discussion combined with a literature review was a follow-up to a meeting, which took place in May 2015. The panel reviewed evidence on use of CGM in 3 potential inpatient scenarios: (1) the intensive care unit (ICU), (2) non-ICU, and (3) transitioning outpatient CGM use into the hospital setting. Panel members agreed that data from limited studies and theoretical considerations suggested that use of CGM in the hospital had the potential to improve patient clinical outcomes, and in particular reduction of hypoglycemia. Panel members discussed barriers to widespread adoption of CGM, which patients would benefit most from use of this technology, and what type of outcome studies are needed to guide use of CGM in the inpatient setting.